Similar Elimination Rates of Glucagon-Like Peptide-1 in Obese Type 2 Diabetic Patients and Healthy Subjects - Vilsbøll, T.; Agersø, H.; Krarup, T.; Holst, J. J. (The journal of clinical endocrinology and metabolism, 2003)
We have previously shown that type 2 diabetic patients have decreased plasma concentrations of glucagon-like peptide 1 (GLP-1) compared with healthy subjects after ingestion of a standard mixed meal. This decrease could be caused by differences in the metabolism of GLP-1. The objective of this study was to examine the pharmacokinetics of GLP-1 in healthy subjects and type 2 diabetic patients after iv bolus doses ranging from 2.5–25 nmol/subject. Bolus injections iv of 2.5, 5, 15, and 25 nmol of GLP-1 and a meal test were performed in six type 2 diabetic patients [age, mean (range): 56 (48–67) yr; body mass index: 31.2 (27.0–37.7) kg/m2; fasting plasma glucose: 11.9 (8.3–14.3) mmol/liter; hemoglobin A1C: 9.6 (7.0–12.5)%]. For comparison, six matched healthy subjects were examined. Peak plasma GLP-1 concentrations increased linearly with increasing doses of GLP-1 and were similar for type 2 diabetic patients and healthy subjects. The peak concentrations of total GLP-1 (C-terminal) after 2.5, 5, 15, and 25 nmol of GLP-1 were 357 ± 56, 647 ± 141, 1978 ± 276, 3435 ± 331 pmol/liter in the type 2 diabetic patients and 315 ± 37, 676 ± 64, 1848 ± 146, 3168 ± 358 pmol/liter, respectively, in the healthy subjects (not statistically significant). Peak concentrations of the intact GLP-1 peptide (N-terminal) were: 69 ± 17, 156 ± 44, 703 ± 77, and 1070 ± 117 pmol/liter in the type 2 diabetic patients and 75 ± 14, 160 ± 40, 664 ± 79, 974 ± 87 in the healthy subjects (not statistically significant). GLP-1 was eliminated rapidly with clearances of intact GLP-1 after 2.5, 5, 15, and 25 nmol of GLP-1 amounting to: 9.0 ± 5.0, 8.1 ± 6.0, 4.0 ± 1.0, 4.0 ± 1.0 liter/min in type 2 diabetic patients and 8.4 ± 4.2, 7.6 ± 4.5, 5.0 ± 2.0, 5.0 ± 1.0 liter/min in healthy subjects. The volume of distribution ranged from 9–26 liters per subject. No significant differences were found between healthy subjects and type 2 diabetic subjects. We conclude that elimination of GLP-1 is the same in obese type 2 diabetic patients and matched healthy subjects. The impaired incretin response seen after ingestion of a standard breakfast meal must therefore be caused by a decreased secretion of GLP-1 in type 2 diabetic patients.